STUDY OF SOCIOLOGY OF LITERATURE IN THE COLLECTION OF SHORT STORIES KANG MAKSUM BY A. MUSTOFA BISRI - Surastina Surastina; Effrina Yuricki (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
This research aims to understand and describe the sociology of literature is a collection of short stories Kang Maksum work of A. Mustofa Bisri starting from the content, themes, and goals. This qualitative research used a description model. The author used A. Mustofa Bisri's collection of Kang Maksum short stories to be subjected to the study. The data collection technique used is a documentation technique. Data analysis in this study is carried out in a qualitative descriptive manner, namely by way of interpretation, analysis, and evaluation. Studied from the point of view of literary sociology, the content of Kang Maksum short story by A. Mustofa Bisri shows a picture of social life that is experienced by the author of his own short story, namely A. Mustofa Bisri. Broadly speaking, the short stories are written want to convey some advice to readers that simplicity in life should be upheld as a principle of life. Each short story is themed on simplicity, social care, concern for the environment, luxury behind simplicity, ambitious attitudes in socio-political life to realize the nation's dream, and the need for values of obedience to God in life. Social topics raised by A. Mustofa Bisri in short stories also play a role in learning for readers as well as a picture of the social life of every community in an area.